Institutional and policy process for climate-smart agriculture: Evidence from Nagaland State, India - Patra, Nirmal K.; Babu, Suresh Chandra (IWA Publishing, 2023)
A critical global policy question is how the environmental management interventions could be repurposed to meet the sustainable development goals and their target for food security, climate protection, and environmental sustainability. A common challenge facing food systems in developing countries is to improve agricultural productivity to ensure food security for all without increasing the emission of greenhouse gases (GHGs) from agriculture. Climate-smart agriculture (CSA) approaches help to reduce GHG emissions from agriculture and address the challenges of climate change (CC) and food insecurity. Yet, CSA lack understanding of the institutional arrangements and policy processes. This paper examines 38 aspects to assess the institutional and policy status for CC mitigation and adaptation and CSA in Nagaland, India. Furthermore, we use these aspects to develop a scale to measure the policy and institutional environment for mitigation and adaptation of CC and implementation of CSA. Nagaland is relatively in a better position in nine aspects, although it can improve. Methodologically, the scale developed in this paper and the identified factors can help study the institutional and policy status of a country, state, or region. We identify several implications for understanding CC and CSA institutions and policies for informing policy research and practice.